A new species of the scale insect genus Newsteadia Green (Hemiptera: Coccomorpha: Ortheziidae) from China - Zheng, Xinyi; Xing, Jichun (Zootaxa, 2021)
Members of the scale insect family Ortheziidae (Hemiptera: Sternorrhyncha: Coccomorpha) occur all over the world but these small, delicate insects are difficult to find. The largest genus in the Ortheziidae is Newsteadia Green. Previous studies have recorded four species of Newsteadia in China. This study describes and illustrates the adult female, male, prepupal male, and first-, second- and third-instar nymphs of a fifth species, Newsteadia fanjingensis sp. n., from Guizhou Province, China, collected above 2000 m altitude under thick moss on the bark of Acer sp. Identification keys are provided to the adult females of Newsteadia species known in China, and the adult males known worldwide.